The major determinant of exendin-4/glucagon-like peptide 1 differential affinity at the rat glucagon-like peptide 1 receptor N-terminal domain is a hydrogen bond from SER-32 of exendin-4* - Mann, RJ (Blackwell Publishing Ltd, 2010)
BACKGROUND AND PURPOSE: Exendin-4 (exenatide, Ex4) is a high-affinity peptide agonist at the glucagon-like peptide-1 receptor (GLP-1R), which has been approved as a treatment for type 2 diabetes. Part of the drug/hormone binding site was described in the crystal structures of both GLP-1 and Ex4 bound to the isolated N-terminal domain (NTD) of GLP-1R. However, these structures do not account for the large difference in affinity between GLP-1 and Ex4 at this isolated domain, or for the published role of the C-terminal extension of Ex4. Our aim was to clarify the pharmacology of GLP-1R in the context of these new structural data. EXPERIMENTAL APPROACH: The affinities of GLP-1, Ex4 and various analogues were measured at human and rat GLP-1R (hGLP-1R and rGLP-1R, respectively) and various receptor variants. Molecular dynamics coupled with in silico mutagenesis were used to model and interpret the data. KEY RESULTS: The membrane-tethered NTD of hGLP-1R displayed similar affinity for GLP-1 and Ex4 in sharp contrast to previous studies using the soluble isolated domain. The selectivity at rGLP-1R for Ex4(9–39) over Ex4(9–30) was due to Ser-32 in the ligand. While this selectivity was not observed at hGLP-1R, it was regained when Glu-68 of hGLP-1R was mutated to Asp. CONCLUSIONS AND IMPLICATIONS: GLP-1 and Ex4 bind to the NTD of hGLP-1R with similar affinity. A hydrogen bond between Ser32 of Ex4 and Asp-68 of rGLP-1R, which is not formed with Glu-68 of hGLP-1R, is responsible for the improved affinity of Ex4 at the rat receptor.